Effect of Aging on Human Mesenchymal Stem Cell Therapy in Ischemic Cardiomyopathy Patients - Golpanian, Samuel; El-Khorazaty, Jill; Mendizabal, Adam; DiFede, Darcy L.; Suncion, Viky Y.; Karantalis, Vasileios; Fishman, Joel E.; Ghersin, Eduard; Balkan, Wayne; Hare, Joshua M. (Journal of the American College of Cardiology, 2015)
The role of patient age in the efficacy of mesenchymal stem cell (MSC) therapy in ischemic cardiomyopathy (ICM) is controversial. This study sought to determine whether the therapeutic effect of culture-expanded MSCs persists, even in older subjects. Patients with ICM who received MSCs via transendocardial stem cell injection (TESI) as part of the TAC-HFT (Transendocardial Autologous Cells in Ischemic Heart Failure) (n = 19) and POSEIDON (Percutaneous Stem Cell Injection Delivery Effects on Neomyogenesis) (n = 30) clinical trials were divided into 2 age groups: younger than 60 and 60 years of age and older. Functional capacity was measured by 6-min walk distance (6MWD) and quality of life using the Minnesota Living With Heart Failure Questionnaire (MLHFQ) score, measured at baseline, 6 months, and 1 year post-TESI. Various cardiac imaging parameters, including absolute scar size, were compared at baseline and 1 year post-TESI. The mean 6MWD was similar at baseline and increased at 1 year post-TESI in both groups: 48.5 ± 14.6 m (p = 0.001) for the younger and 35.9 ± 18.3 m (p = 0.038) for the older participants (p = NS between groups). The older group exhibited a significant reduction in MLHFQ score (−7.04 ± 3.54; p = 0.022), whereas the younger than 60 age group had a borderline significant reduction (−11.22 ± 5.24; p = 0.058) from baseline (p = NS between groups). Although there were significant reductions in absolute scar size from baseline to 1 year post-TESI, the effect did not differ by age. MSC therapy with TESI in ICM patients improves 6MWD and MLHFQ score and reduces myocardial infarction size. Importantly, older individuals did not have an impaired response to MSC therapy.